ANALYSIS THE INFLUENCE OF MOTIVATION AND JOB SATISFACTION ON THE SUSTAINABILITY OF EMPLOYEE PERFORMANCE AT SICEPAT EKSPRESS MAJALENGKA BRANCH - Sudibyo Budi Utomo; Yelsha Dwi Pasca (STIESA Press, 2025)
This study aims to determine the picture of motivation, job satisfaction, and employee performance at Sicepat Ekspres Cabang Majalengka and to determine the effect of motivation and job satisfaction on the performance of Sicepat Ekspres Cabang Majalengka employees. The research method used is a descriptive and verification method using a quantitative research approach. This research data is primary data obtained through the distribution of questionnaires. The total population and sample of this study amounted to 31 respondents. The sampling technique in this study used saturated samples. The results of research processed with the SPSS Version 26.00 for Windows program show that a multiple correlation value of 0.635 means that motivation and job satisfaction with employee performance have a strong relationship. The value of the coefficient of determination obtained an adjusted R square value of 40.4% showing the amount of contribution of the independent variables (motivation and job satisfaction) to employee performance, while the remaining 59.6% can be explained by factors other than those studied in this study. The results of the simultaneous test (Test F) showed a significance value of 0.01 < 0.05, Motivation (X1) and Job Satisfaction (X2) simultaneously had a positive and significant effect on Employee Performance (Y) at Sicepat Ekspres Cabang Majalengka. The results of the partial test (Test T) show that the value of motivational significance (X1) is 0.005 < 0.05 the value of t is calculated as 3.010 > t Table 1.699 means that motivation has a positive and significant effect on employee performance (Y), significant value of job satisfaction (X2) 0.004 < 0.05 calculated value of 3.126 < t table 1.699 This means that job satisfaction has a positive and significant effect on employee performance (Y) at Sicepat Ekspres Majalengka.